Journey to the West - Mohammad Zuhairee Ramlan (2016)
“Journey to the West”, is a project inspired by personal experiences between three individuals who travel to the west side of Singapore on a daily basis. A typical journey that most individuals face as they travel to work, school, or just to get from one place to another. This story revolves greatly around Singapore’s environment; aimed to reach out to the locals, and enabling them to associate this film with the problems they face while commuting - parodying our usual angry aunties, obnoxious uncles and some stereotypical humor. The film hopes to reach out the international audiences as well, as train commuting is a common part of peoples’ lives in general.